2014
DOI: 10.1123/jab.2013-0085
|View full text |Cite
|
Sign up to set email alerts
|

Shank-Rearfoot Joint Coupling with Chronic Ankle Instability

Abstract: Chronic ankle instability (CAI) results in longstanding symptoms and subjective feelings of "giving way" following initial ankle sprain. Our purpose was to identify differences in joint coupling and variability between shank internal/external rotation and rearfoot inversion/eversion throughout the gait cycle of CAI subjects and healthy controls. Twenty-eight young adults participated (CAI, n = 15, control, n = 13). Kinematics were collected while walking and jogging on a treadmill. A vector coding method in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…Overall findings revealed that 73% (n = 16/22) of studies reported a statistically significant difference in at least one dependent variable used to examine movement variability between injured subjects and uninjured controls. Injured subject groups demonstrated greater variability in 64% (n = 14/22) of the studies, reduced variability in 27% (n = 6/22), and no difference between groups was evident in 27% (n = 6/22) . Table presents the percentage of studies reporting greater, less, or no difference in variability when comparing injured subjects to uninjured controls.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall findings revealed that 73% (n = 16/22) of studies reported a statistically significant difference in at least one dependent variable used to examine movement variability between injured subjects and uninjured controls. Injured subject groups demonstrated greater variability in 64% (n = 14/22) of the studies, reduced variability in 27% (n = 6/22), and no difference between groups was evident in 27% (n = 6/22) . Table presents the percentage of studies reporting greater, less, or no difference in variability when comparing injured subjects to uninjured controls.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies investigating single specific injuries, 88% (n = 14/16) reported significant between‐group differences. Of these, greater variability was evident in 75% (n = 12/16), reduced variability in 31% (n = 5/16), while 13% (n = 2/16) reported no significant differences between injured and uninjured groups . Table presents the breakdown of findings when specific injury types were group together.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations